2003
DOI: 10.1097/01.tp.0000093996.96158.44
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous familial hypercholesterolemia: specific indication for domino liver transplantation

Abstract: Domino transplantation can be efficiently used in a patient with marginal indications for transplantation using a liver from a patient with FHC. The slightly elevated serum cholesterol level in the recipient may be explained by the normal function of extrahepatic LDL-R.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 23 publications
(19 reference statements)
3
26
0
Order By: Relevance
“…When hepatic inadequacy occurred because of liver cancer and chronic liver disease, form, esterification and evacuation of cholesterol were blocked, which causes changes of plasma cholesterol level (Cooper et al, 1996;Motta et al, 2001;Ooi et al, 2005;Heeren et al, 2004;Kanel et al, 1983;Popescu et al, 2003); and it was also discovered that serum cholesterol level was negative correlated with occurrence and mortality of some cancers by epidemiologic study (Law and Thompson, 1991;Williams et al, 1981). Study of the correlation between total serum cholesterol and tumor showed that the cholesterol level in patients who died of cancer was significantly lower than that in those who survived (Cambien et al, 1980).…”
Section: Influence Of Liver Cancer On Choles-terol Metabolismmentioning
confidence: 99%
“…When hepatic inadequacy occurred because of liver cancer and chronic liver disease, form, esterification and evacuation of cholesterol were blocked, which causes changes of plasma cholesterol level (Cooper et al, 1996;Motta et al, 2001;Ooi et al, 2005;Heeren et al, 2004;Kanel et al, 1983;Popescu et al, 2003); and it was also discovered that serum cholesterol level was negative correlated with occurrence and mortality of some cancers by epidemiologic study (Law and Thompson, 1991;Williams et al, 1981). Study of the correlation between total serum cholesterol and tumor showed that the cholesterol level in patients who died of cancer was significantly lower than that in those who survived (Cambien et al, 1980).…”
Section: Influence Of Liver Cancer On Choles-terol Metabolismmentioning
confidence: 99%
“…Since then, more than 540 cases of DLTx have been performed using FAP domino grafts, mostly in Europe (2). Three other kinds of domino liver grafts for metabolic disorders have also been reported, including primary hyperoxaluria (3), HFH (4) and MSUD (5). This report is to describe a domino liver transplantation using an HFH liver as a domino graft with successful results.…”
mentioning
confidence: 99%
“…In some cases, the recipient of the domino graft will express serious consequences of the disease afflicting the domino donor, as in the case of hyperoxaluria. 17 In other cases, the recipient of the domino transplant seems to have enough of a delay in onset of symptoms, as in the case of familial amyloid polyneuropathy, or sufficiently attenuated symptoms, as in the case of familial hypercholesterolemia, 18 to make domino transplantation worth considering in cases where the survival of the final recipient is questionable in the time frame for organ procurement through routine channels.…”
mentioning
confidence: 99%